GEOLOGI BAWAH PERMUKAAN FORMASI CIKAPUNDUNG BERDASARKAN ANALISIS GEOLISTRIK DI DESA CIPICUNG, MANGGAHANG, KECAMATAN BALE ENDAH, KABUPATEN BANDUNG - -, Undang Mardiana (Fakultas Teknik Geologi Universitas Padjadjaran, 2006)
Sub-District Of Manggahang, District of Bale Endah have hilly and plain morphology with enough difference of height. Geologically is compiled by volcanic rock which consist of brecia, tuff, and lava which product of Old Volcanic. It is included in Cikapundung Formation which Middle Plistosen age (Silitonga, 1979) and lake sediment representing interval of fine clasticas clayey tuff, silty tuff, locality is found the existence of plant pickings, fine-coarse sandstone till with congelation rock fragment, this sediment is Quater age.Based on resistivity value, rock stratigraphy in study area have resisitivity which vary start from value set of Ωm (soil), tens of Ωm (brecia/tuff weathered), hundreds of Ωm (brecia-tuff), thousands of Ωm (lava 1), tens of thousand Ωm (lava 2), and hundreds of thousand Ωm (lava 3), third of him represent of andesitic lava (porfiry andesit at upper, and porfiry diorit at bottom).At high elevation covered by soil which thiner than foot-hill with spreading follow topography. Bellow of soil are interval of brekcia and tufa disseminating until assumption point GL - 02. and more thinning at foot area (to southern). Below interval of brecia and tuf, there are andesitic lava. At top hill, there is lava at 800 m elevation and in GL-02 having elevation 700 m. Hence if taken by elevation 700 m representing boundary of lower elevation, hence is andesitic lava from 100 m till 10 m.